Hello! :)
To solve your equation, we will first simplify both sides of the equation
-7 = -1 + x/3
-7 = -1 + 1/3x
-7 = 1/3x - 1
Next, we will flip the equation
1/3x - 1 = -7
Third, we will add 1 to both sides
1/3x - 1 + 1 = -7 + 1
1/3x = -6
Last, we will Multiply both sides by 3
3 * (1/3x) = (3) * (-6)
x = -18 (ANSWER)
That means -18 is you answer
Hope this helped you!
THEDIPER
A the first answer because the triangles are the same they are just flipped
Answer:
m<NQS = 32°
Step-by-step explanation:
Given:
m<BQS = 80°
m<BQN = 48°
Required:
m<NQS
SOLUTION:
Angle BQN and angle NQS are adjacent angles having a common line, QN, and a common corner point, Q.
Therefore:
m<BQN + m<NQS = m<BQS (angle addition postulate)
48° + m<NQS = 80° (substitution)
m<NQS = 80 - 48° (Subtraction of 48 from each side)
m<NQS = 32°